How do lung cancer specialists follow their patients with stage III non-small cell lung cancer (NSCLC) after definitive treatment? - A short report - YUMUK, PERRAN FULDEN (ELSEVIER SCI LTD, 2012)
Although pretreatment evaluations are well defined for the diagnosis of radically treatable NSCLC, we have very little data about the follow-up of these patients after completion of therapy, especially for stage III patients. No documented standards for surveillance were set in the NCCN, ACCP or ESMO guidelines. In order to determine the standard practice patterns of lung specialists, a survey was done. Physicians were asked which tests they do for pretreatment evaluation and also on asymptomatic patients during their post-treatment follow-up. The survey was sent to 192 centres which were part of the EORTC Lung Cancer Group. Thirty-eight centres from 12 different countries replied. Results showed that almost all the centres are doing very similar pretreatment evaluation procedures in stage III NSCLC. In the post-treatment follow-up setting, results were more varied in terms of frequency and type of scans used. The most commonly used test was a computed tomography (CT) of the chest and abdomen at 3 months post-treatment. Positron emission tomography (PET)/CT and magnetic resonance imaging (MRI) of the brain with contrast were done only in symptomatic patients. This audit suggests that one CT scan at 3 months after the end of radical treatment has become a standard with little evidence showing it is better than a chest radiography (CXR). These data should be used to encourage research into molecular parameters or new imaging techniques that could be tested as more sensitive methods of picking up relapse in radically treated stage IIIA patients who has a high relapse rate in the first 12 months. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Carcinoma; Non-small-cell lung; Questionnaires; Positron-emission tomography and computed tomography